2019
DOI: 10.3390/molecules24224061
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Dextran as a Macromolecular Crosslinker Stabilizes the Zein/Caseinate Nanocomplex for the Potential Oral Delivery of Curcumin

Abstract: In this study, we prepared complex nanoparticles from a combination of two proteins and one polysaccharide for the encapsulation and delivery of lipophilic bioactive compounds. Two proteins, zein and sodium caseinate (NaCas), provided a hydrophobic core for the encapsulation of a lipophilic compound (curcumin), while a polysaccharide dialdehyde, oxidized dextran, served as the coating material and macromolecular crosslinker to create covalent linkage with two proteins for stabilization purposes. The heating ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…In this study, thioflavin‐S staining showed that curcumin treatment did not affect the plaque load in the hippocampus of transgenic mice. Nevertheless, the activation of astrocyte cells was suppressed by curcumin treatment in our study, which is in line with a previous report by Lim 30 . A preliminary investigation of the possible mechanisms of curcumin action was performed.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, thioflavin‐S staining showed that curcumin treatment did not affect the plaque load in the hippocampus of transgenic mice. Nevertheless, the activation of astrocyte cells was suppressed by curcumin treatment in our study, which is in line with a previous report by Lim 30 . A preliminary investigation of the possible mechanisms of curcumin action was performed.…”
Section: Discussionsupporting
confidence: 93%
“…The protective effect of curcumin may be mediated by the inhibition of NF‐κB activation 40 and/or an antioxidant pathway 27 . Oral administration of curcumin reduces inflammatory cytokines and oxidized proteins 30,41 and attenuates behavioural impairment in AD animal models 42 . There is a low basal COX2 expression in neurons of the healthy brain; however, pathological conditions, such as astrocyte activation, strongly induce COX2 in the brain 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dead cells could be desorbed from the hydrogels by cooling the system to 25 °C and adding 50 mM phosphate buffered saline (PBS) pH 7.4, enabling the reusability of the hydrogels [314]. Dextran dialdehyde (MW ~40,000 g/mol) prepared from the oxidation of dextran by sodium periodate [315] reacted with zein and sodium caseinate by imine bond formation (Shiff base reaction), increasing the system stability [316].…”
Section: Macromolecular Crosslinkersmentioning
confidence: 99%
“…Dextran T10, T40 and T2000 (Mw 10, 40 and 2000 kDa) were obtained from Pharmacia (Uppsala, Sweden), gelatine 45% w/v solution (from cold water fish) and glutaraldehyde (GA) 25% v/v aqueous solution were purchased from Sigma (Steinheim, Germany). The DDA was prepared and characterized according to previously published methods [45,59].…”
Section: Chemicalsmentioning
confidence: 99%